Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1248/bpb.30.1003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Properties of Lafutidine after Postprandial Oral Administration in Healthy Subjects: Comparison with Famotidine

Abstract: Lafutidine, 2-(furfurylsulfinyl)-N-[4-[4-(piperidinomethyl)-2-pyridyl]oxy-(Z)-2-butenyl] acetamide, is a newly developed histamine H 2 -receptor antagonist. It is at present only approved in Japan as a tablet, and is used in the treatment of gastric ulcers, duodenal ulcers, and gastric mucosal lesions associated with acute gastritis and acute exacerbation of chronic gastritis.1) Lafutidine possesses a potent and longlasting gastric antisecretory effect mediated by H 2 -receptor blockade in animals.2) Lafutidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…A number of analytical methods have been reported for the determination of individual H 2 antagonists in human plasma since 1990 years, cimetidine [1][2][3][4][5][6][7][8], ranitidine [9][10][11][12][13][14][15][16][17], famotidine [18][19][20][21][22][23][24][25], and lafutidine [26][27][28][29]. Apart from some uncommonly used methods such as free capillary zone electrophoresis [4], micellar electrokinetic capillary chromatography [7], HPTLC [13], most reports utilized HPLC-UV method [1][2][3][4][5][6][7][9][10][11][12][13][14][15][16][18][19]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of analytical methods have been reported for the determination of individual H 2 antagonists in human plasma since 1990 years, cimetidine [1][2][3][4][5][6][7][8], ranitidine [9][10][11][12][13][14][15][16][17], famotidine [18][19][20][21][22][23][24][25], and lafutidine [26][27][28][29]. Apart from some uncommonly used methods such as free capillary zone electrophoresis [4], micellar electrokinetic capillary chromatography [7], HPTLC [13], most reports utilized HPLC-UV method [1][2][3][4][5][6][7][9][10][11][12][13][14][15][16][18][19]…”
Section: Introductionmentioning
confidence: 99%
“…Apart from some uncommonly used methods such as free capillary zone electrophoresis [4], micellar electrokinetic capillary chromatography [7], HPTLC [13], most reports utilized HPLC-UV method [1][2][3][4][5][6][7][9][10][11][12][13][14][15][16][18][19][20][21][22][23]26,27]. Although HPLC method is mature and relatively economical, limitations such as sensitivity, selectivity and throughput were often encountered during the method development.…”
Section: Introductionmentioning
confidence: 99%
“…Many published comparative clinical studies have established the superiority of lafutidine over proton pump inhibitors [2,6,16] and other H2-receptor antagonists [1,25] . The normal dose of lafutidine is 10 mg once a day for gastric mucosal lesions associated with acute gastritis and acute exacerbation of chronic gastritis; 10 mg once a day as a preanesthetic medication; and 10 mg twice a day for gastric ulcers, duodenal ulcers and stomal ulcers [20] .…”
Section: Discussionmentioning
confidence: 99%
“…An internationally published pharmacokinetic study of lafutidine performed on healthy Japanese male volunteers showed a Cmax of 133.90 ng/mL and tmax of 1.84 h [1] . A similar study performed on healthy Chinese volunteers showed a Cmax of 151.55 ± 54.49 ng/mL and tmax of 1.60 ± 0.40 h [26] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation